Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic

Study on anisotropy in wire arc additively manufactured Inconel 625 multi-layered wall and its correlation with molten pool thermal history - Nagallapati, Vishwanath; Choudhary, Amit; Torris, Arun; Muvvala, Gopinath; Dadasaheb, Sagar Pawar; Gudur, Srinath Ellaswamy (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
In the present study, the variation in molten pool thermal history with layer number during wire arc additive manufacturing of Inconel 625 wall was investigated. Further, its effect on the evolution of microstructure and anisotropy in mechanical and corrosion properties was reported. During the deposition process, the molten pool thermal history was monitored using a non-contact type IR pyrometer operating at 1.6 mu m wavelength. A total number of 40 layers were deposited, building a wall of 60 mm height. With an increase in layer number, the molten pool lifetime and cooling rate were found to increase and decrease, respectively, resulting in coarse grains and increased elemental segregation or Laves phase formation. To investigate its effect on mechanical properties, the samples were collected in a skewed fashion along the height with orientation in the deposition direction. The tensile specimens collected close to the substrate exhibited better strength and ductility, while the samples from the top location of the wall exhibited a relatively brittle mode of fracture, which was investigated by carrying out the fracture surface analysis using SEM. Corrosion test was also conducted along the height of the wall, wherein the samples close to substrate exhibited better corrosion resistance due to refined microstructure and low elemental segregations. Further, EDS, XRD analysis and hardness test were carried out to investigate the elemental composition, variation in phases and hardness with layer number, respectively.
Keywords: anisotropy; Layer number; mechanical properties; Molten pool thermal history; Wire arc additive manufacturing

Investigating the ferrimagnetic behaviour of trigonal 3C Fe7S8 nanoparticles - Jyotsna, Shubhra; Poddar, Pankaj (Bulletin of Materials Science, 2023)
The magnetic properties of trigonal 3C Fe7S8 nanoparticles, synthesized via the thermal decomposition method, are investigated using temperature-dependent zero-field cooled (ZFC) and field-cooled (FC) magnetization (M-T) curves. The M-T data, recorded at 100 and 1000 Oe, reveal magnetic ordering with high Curie transition temperature (T-C > 300 K) in the specimen. The magnetization vs. applied magnetic field (M-H) data measured in the temperature range from 7 to 300 K show that the compound exhibits ferrimagnetic ordering. The values of coercivity (H-C), saturation magnetization (M-60 kOe) and remanent magnetization (M-R) appear to increase at lower measuring temperatures. As the result of increasing M-60 kOe at lower measuring temperatures, within the temperature range of 7 to 300 K, the maximum energy product (BHmax) has the highest value of 128 kG Oe at 7 K.
Keywords: anisotropy; energy product; Fe7S8; ferrimagnetism; Pyrrhotites; trigonal phase